Ag doping induced abnormal lattice thermal conductivity in Cu2Se. Issue 48 (27th November 2018) - Liu, Weidi; Shi, Xiaolei; Hong, Min; Yang, Lei; Moshwan, Raza; Chen, Zhi-Gang; Zou, Jin
Abstract : Schematic diagram of Cu + /Ag + diffusion in the Se sublattice of Cu2 Se, in which blocked diffusion of Ag + may subsequently block the diffusion of other Cu + and weaken the scattering of phonons. Abstract : Superionic Cu2 Se-based thermoelectric materials have attracted extensive attention in recent years due to their ultralow lattice thermal conductivity and high dimensionless figure of merit ( zT ). Inspired by the effectiveness of heavy-element doping in reducing lattice thermal conductivity in various thermoelectric materials, we investigate the Ag-doping effects on the thermoelectric properties of Cu2 Se nanocrystals made via a facile solvothermal method and subsequently spark plasma sintering. Based on the single parabolic band model analysis of thermoelectric properties, it has been found that the isoelectronic Ag dopant leads to an enhanced carrier concentration and significantly reduced carrier mobility, as well as a reduced electrical conductivity and power factor. Moreover, the reduced disorder-level of cations leads to an extraordinarily enhanced lattice thermal conductivity. All these result in a zT reduction for Ag-doped Cu2 Se. This work systematically studies the influence of Ag dopants on the thermoelectric performance of Cu2 Se and indicates that the Ag-doping is less promising in enhancing it.